Diseño del sistema contable y financiero para las organizaciones campesinas de Cantón Quinsaloma, 2014. - Espinales Suarez, Hamilton Omar (2014)
Peasant organizations consist of 8 organizations from base, one per enclosure Quinsaloma Canton. The legal status of farmers' organizations is a cantonal Union of peasant and indigenous organizations working with Ministerial Agreement No. delegated by the Ministry of Agriculture, Livestock, Aquaculture and Fisheries (MAGAP). This research was made due to the lack of an accounting and financial system FOs Canton Quinsaloma since for various reasons have not been able to bring in an adequate manner the accounts within each organization, which was raised the following objectives: Develop a system for accounting and financial FOs Quinsaloma Canton: a diagnosis of administrative, operational activities of the accounting and financial control of farmers 'organizations, establish procedures to farmers' organizations; control activities in the administrative, operational and financial management and propose an accounting and financial system of the Canton FOs to strengthen Quinsaloma making administrative, operational and financial decisions. These FOs have an internal structure that are formed as demonstrated by its statutes by their boards: the president, secretary, treasurer and three members elected by secret ballot by the general meeting being responsible for the registration of commercial transactions, administrative and treasurers operating with the help of secretaries who performs functions or activities and perform tasks beyond their competence, these financial reports are submitted and disseminated to the partners at the end of the year. The meetings of the board of FOs are convened by its directives end of each month in order to collect contributions of each partner and discuss aspects of the progress of work of those awarded productive projects of the Provincial Government of Rivers Area North. Being the most important decisions in peasant organizations that have been characterized to undertake and promote productive projects. Through deep in each of the eight farmer organizations Canton Quinsaloma with legal MAGAP supported by the analysis applies a inefficient accounting, directly harming the partners, they do not have a safety or confidence in the results that are achieved by fiscal year end. Peasant organizations are working only with basic and simple records, which at the time of the balance causes problems and confusion. Within every organization there is a statute which are formed by the provisions of the Organic Law of the People and Solidarity Economy and Financial Popular and Solidarity Sector, its General Regulation, issued by the regulator and the Superintendency of Popular and Solidarity Economy that 87% of members are unaware of the regulations for the performance of their association and 13% know it, ie not applying accounting policies set out in the only catalog issued by the Superintendency of Popular Solidarity Economy. Lacking this unique catalog issued by the Superintendency of Popular and Solidarity Economy, no tools needed to make important decisions in organizations and can not regularly report on the financial statements to the shareholders; why is proposed in the proposed design FOs achieve make better management decisions and have an accounting control and financial resources in order to optimize organizations as accounting and financial system.